Borderless - De Leon, Jennifer, 1979- (New York : Atheneum, 2023)
Caught in the cross hairs of gang violence, seventeen-year-old fashion designer, Maya, and her mother set off on a perilous journey from Guatemala City to the US-Mexico border.
"A Caitlyn Dlouhy book."
new ya book 2025 winter.
Ages 14 up.
Grades 10-12.
Keywords: Fashion design -- Fiction; Urban violence -- Fiction; Mothers and daughters -- Fiction; Gangs -- Fiction; Mexican-American Border Region -- Fiction; Guatemala (Guatemala) -- Fiction